2016
DOI: 10.1037/xge0000199
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genuine eye contact on visuospatial and selective attention.

Abstract: We investigated performance in a visuospatial discrimination task and selective attention task (Stroop task) while a live person's direct or averted gaze was presented as a task-irrelevant contextual stimulus. Based on previous research, we expected that response times to peripherally presented targets (Experiment 1) and to the Stroop stimuli (Experiment 2) would be longer in the context of direct versus averted gaze. Contrary to our expectations, the direct gaze context resulted in faster discrimination of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 14 publications
6
37
0
Order By: Relevance
“…The observation that, in Experiment 2, eye contact led to an overall decrement in saccadic latencies resembles the pattern described in a recent study reporting that participants reacted more readily to peripheral targets after making eye contact with a real individual 54 . According to the authors, this might be due to the enhanced levels of arousal that are typically elicited by eye contact episodes which, in turn, would lead participants to be more prone to react to the onset of visual stimuli.…”
Section: Discussionsupporting
confidence: 82%
“…The observation that, in Experiment 2, eye contact led to an overall decrement in saccadic latencies resembles the pattern described in a recent study reporting that participants reacted more readily to peripheral targets after making eye contact with a real individual 54 . According to the authors, this might be due to the enhanced levels of arousal that are typically elicited by eye contact episodes which, in turn, would lead participants to be more prone to react to the onset of visual stimuli.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with previous studies demonstrating the influence of specific social cues during interactions (such as direct eye gaze) on learning, that is, in typical participants, direct eye gaze enhances cognitive performance. Although the mechanisms behind this relation seem to be very complex, involving the effects on motivation, arousal, and attention (Hietanen et al., ; Kuhl, ; Kylliäinen et al., ), we demonstrated that MG during interactions is related to the development of attention disengagement. We propose that the effect of MG on attention disengagement reported here may be driven by the impact of MG on the orienting network, which includes gaze disengagement and shifting (Johnson et al., ; Colombo, ; Johnson & de Haan, , chapter 5) and selective attention (Mesulam, ).…”
Section: Discussionsupporting
confidence: 53%
“…Direct gaze of a live model (contrary to a picture) elicits higher levels of autonomic arousal than averted gaze or closed eyes. In consequence, participants show faster discrimination of visual targets and faster performance in the Stroop task in the direct gaze condition compared to the averted gaze condition (Hietanen, Myllyneva, Helminen, & Lyyra, ).…”
Section: Mutual Gaze and Learning In The Context Of Social Interactionsmentioning
confidence: 99%
“…Specifically, they have suggested that attention explains the startle reflex attenuation to probes presented with short delays after foreground stimuli (SOAs shorter than 300 ms); but at longer delays (SOAs longer than 800 ms), when the foreground stimuli have been recognized and encoded, the defensive or appetitive motivational system is activated and modulates the reflex. Second, a previous study from our laboratory showed that discrimination of peripheral, irrelevant visual stimuli presented after live faces (using the same methodology as in FIGU RE 3 Mean HR changes to the startle probe when viewing direct and downward gaze within the 6-s time interval across the short and long SOAs the present study) was more enhanced after direct than averted gaze (Hietanen, Myllyneva, Helminen, & Lyyra, 2016). The result was explained by the effect of direct gaze on arousal and attention.…”
Section: Discussionsupporting
confidence: 53%